Impact of tax justice on tax compliance Field study - سليمان هديل; حسين عبد الله (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of this research is to learn about the impact of the administration of justice, which is one of the most important determinants of good tax governance on tax compliance in Syria. The descriptive analytical curriculum was used to build the problem of this research and develop its hypotheses. Appropriate research tools have also been used: personal interviews with some tax administration workers and employers of commissioners, the identification tool to collect data from a sample of large and medium income tax in the Syrian coast that measures the availability of this determinant, and the analysis of data using the statistical program SPSS. The results of this research showed a dramatic decline in both taxpayers’ level of compliance, taxpayers’ confidence in tax administration, as well as a marked weakness in perceptions of justice. The study found a set of recommendations that, if applied, could strengthen the determinants of good tax governance (fairness) and improve the level of compliance of the mandate holders. At a time when it can serve as an input to the desired tax reform.